1984
DOI: 10.1080/07391102.1984.10507524
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Resonance Raman Spectroscopy to the Identification of Z DNA

Abstract: Poly(dG-dC).poly(dG-dC) at low salt concentration (0.1 M NaCl) and at high salt concentration (4.5 M NaCl) has been studied by Raman resonance spectroscopy using two excitation wavelengths: 257 nm and 295 nm. As resonance enhances the intensity of the lines in a proportion corresponding to the square of the molar absorption coefficient, the intensities of the lines with 295 nm wavelength excitation are enhanced about sevenfold during the B to Z transition. With 257 nm excitation wavelength the 1580 cm-1 line o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
16
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…Resonance Raman studies of chromophores with visible excitation are well known (1-3), but it is only recently that studies in the ultraviolet region (below 300 nm) have been made for a number of species (5-9) including nucleic acids (9)(10)(11)(12)(13)(14)(15)(16)(17). The resonance Raman excitation profiles of both fundamental and overtone vibrations of the nucleic acid bases have been studied in the region of the first absorption band near 260 nm (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resonance Raman studies of chromophores with visible excitation are well known (1-3), but it is only recently that studies in the ultraviolet region (below 300 nm) have been made for a number of species (5-9) including nucleic acids (9)(10)(11)(12)(13)(14)(15)(16)(17). The resonance Raman excitation profiles of both fundamental and overtone vibrations of the nucleic acid bases have been studied in the region of the first absorption band near 260 nm (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Sci. USA 82 (1985) The importance of Raman spectroscopy as a structural tool in the determination of nucleic acid structure is well known (1-3, 9-17), and it has been shown recently that base vibrations that are resonance-enhanced in the first major absorption band are sensitive to the conformation of nucleic acids in solution (17). It is becoming increasingly evident that DNA conformation information can be obtained from the enhanced vibrations of the chromophoric aromatic portions of nucleic acids.…”
mentioning
confidence: 99%
“…Although the Z form marker bands are weaker than those shown in Miskovsky's paper (29), there is some indication of the presence of left-handed structure in the natural DNA We showed in another paper (30) it is possible to enhance selectively the Z form contribution in resonance Raman spectroscopy (RRS) with an excitation wavelength in the 280-300 nm region. Hence we made some measurements on the same DNA sample in using the 284 nm excitation wavelength.…”
Section: Introductionmentioning
confidence: 75%
“…Datachrom pulsed YAG and dye laser system. Details of the Raman setup and of the acquisition system have been described previously (30)(31)(32).…”
Section: Methodsmentioning
confidence: 99%
“…Some experiments' results indicated that the irradiation could result in destabilizing the DNA structure and decreasing the initial level of DNA lesions. 9,10 Because the DNA has an intricate helical and three-dimensional structure that keeps the DNA stabilization, [11][12][13] the course of the structure of DNA broken by irradiation is complicated and vague.…”
mentioning
confidence: 99%